Pemanfaatan HDPE (High Density Polyethylene) Menjadi Produk Komersial Pada KWT Meuseuraya Sidoarjo - Dhamayanthi, Wenny; YA, Ratih Puspitorini; Wardani, Dyah Kusuma; Andini, Paramita; Hudori, Huda Ahmad; Pratama, Fredy Eka Ardhi; Atmajaya, Aditya Wahyu Winadi (SEJAGAT : Jurnal Pengabdian Masyarakat, 2024)
The Community Service Program at the Meuseuraya Women's Farmers Group (KWT), Lebo Village, Sidoarjo, focuses on utilizing plastic bag waste (HDPE) into handicraft products with economic value. This activity includes field surveys, lectures, tutorials, discussions, practices and monitoring. The survey results show that there is a large amount of plastic waste that is not processed properly, causing environmental problems. Counseling and training were carried out to improve the skills of KWT women in processing plastic waste into products such as plastic flowers, bags and home decorations. Plastic waste selection and sorting processes are also introduced to ensure the quality of raw materials. This activity succeeded in increasing participants' knowledge and skills, as well as providing plastic waste-based entrepreneurship opportunities that can increase family income and reduce negative environmental impacts. KWT mothers showed high enthusiasm in utilizing plastic waste, creating creative products with high selling value.